Dinamika Relasi Islam Dan Negara: Tinjauan Terhadap Kelompok Modernis dan Neo Medernis - Ravico, Ravico (Ampera: A Research Journal on Politics and Islamic Civilization, 2022)
The relationship between Islam and the state in the political journey in Indonesia has a journey and continues to be an endless debate or polemic. So that the next stage of the debate gave birth to two groups of Islamic political thought, namely the modernist and neo-modernist groups. The focus of the problem is how these two groups view the relationship between Islam and the state. This research is a descriptive-qualitative research with literature study and its stages. This study uses a historical approach to find analysis and answers to problems. The result of the research is that the main ideas of the two schools of modernism or neo-modernism in viewing Islam and the state must have fundamental differences, because theoretically, Islam and the state are difficult to find common ground. So that both are divided into 2 (two) thoughts, namely idealistic and realistic. However, in their idealistic framework, they both formulated a state system that was entirely based on Islamic knowledge.